2020
DOI: 10.1055/s-0040-1715093
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Platelet Heterogeneity and Host Immune Response in Coronavirus Disease 2019 (COVID-19)

Abstract: This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…These ndings are concurrent with the fact that COVID-19 is associated with mild thrombocytopenia that is linked with more severe disease and mortality as SARS-CoV-2 can alter platelet number, form, and function. 31,32 Also, MDW was signi cantly correlated with the prothrombin time (PT) (r = 0.174, p < 0.05), activated partial thromboplastin time (APTT) (r = 0.204, p < 0.05), and D-Dimer (r=-0.218, p < 0.05). Studies have reported disturbed coagulation in COVID-19 patients, including decreased antithrombin, prolonged prothrombin time, and increased brin degradation products such as D-dimer.…”
Section: Discussionmentioning
confidence: 97%
“…These ndings are concurrent with the fact that COVID-19 is associated with mild thrombocytopenia that is linked with more severe disease and mortality as SARS-CoV-2 can alter platelet number, form, and function. 31,32 Also, MDW was signi cantly correlated with the prothrombin time (PT) (r = 0.174, p < 0.05), activated partial thromboplastin time (APTT) (r = 0.204, p < 0.05), and D-Dimer (r=-0.218, p < 0.05). Studies have reported disturbed coagulation in COVID-19 patients, including decreased antithrombin, prolonged prothrombin time, and increased brin degradation products such as D-dimer.…”
Section: Discussionmentioning
confidence: 97%
“…This evidence is not unexpected, as platelet biology appears to be largely perturbed in patients with SARS-CoV-2 infection, and further contributes to magnify their risk of developing pulmonary or disseminated thrombosis. 24,25 Although a thoughtful discussion on the interplay between platelets and SARS-CoV-2 infection has already been provided in some previous articles, 24,25 a brief overview on the significance of these findings is perhaps advisable. SARS-CoV-2 can contribute to platelets activation via a variety of mechanisms and different pathways, such as direct binding to platelet surface, provoking endothelial injury, sustaining an inflammation-related release of von Willebrand factor (VWF) compounded by a concomitant decrease in the activity of ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) which would then lead to impaired cleavage of ultralarge VWF, as well as by reducing heparan sulfates at blood vessel surface and impairing generation of vasoeffective mediators (e.g., nitric oxide, prostacyclin, and prostaglandin).…”
mentioning
confidence: 99%
“…[90][91][92] Elevated plasma levels of proinflammatory cytokines such as interleukin (IL)-1α, IL-1β, IL-6, IL-12, monocyte chemoattractant protein-1, interferon-γ, and tumor necrosis factorα have been found in patients with COVID-19. [93][94][95] While there is evidence of elevated proinflammatory cytokines, it is important to note that there are also reports finding similar or lower levels of proinflammatory cytokines when compared with patients with COVID-19-unrelated acute respiratory distress syndrome or other cytokine release syndromes. [96][97][98] In addition, reports have also found elevated D-dimer concentrations in patients with COVID-19, 99 which is consistent with the observed systemic inflammation and macrovascular thrombotic complications seen in patients with SARS-CoV-2 infection, 100,101 and may therefore be linked to coagulation activation and diffuse macroand microvascular thrombosis.…”
Section: The Platelet Response During Sars-cov-2 Infectionmentioning
confidence: 99%